Testing approach and avoidance motives and job satisfaction: psychological contract breach as a moderator of the mediating roles of tactics. Issue 3 (4th February 2017) - Liang, Huai-Liang
Abstract: This study tested the mediating roles of both voice and facades of conformity in the relationship between regulatory foci and job satisfaction and the extent to which the mediating roles is moderated by psychological contract breach among a sample of 271 military recruits in Taiwan. Results suggest that voice and facades of conformity mediated the relationship between regulatory foci and job satisfaction. Also, results suggest that perceived breach moderates this mediating pathway: Strong psychological contract breach increases the relationship between promotion focus and voice in the case of job satisfaction. On the other hand, psychological contract breach strongly moderates the relationship between prevention focus and facades of conformity in the case of low job satisfaction. Results are discussed in view of the importance of (a) including the measure of regulatory focus in future studies, (b) the mediating roles of different tactics in explaining the relationship between regulatory foci and job satisfaction and (c) the moderating role of psychological contract breach as a negative workplace event. Implications for the results are discussed.